Legal Justice Of The Wage Rights Of Honorary Teachers In Indonesia - Khoir, Alafa Nidaul (Widya Yuridika, 2024)
Teachers are an important aspect of education because the success of students depends on the teacher's teaching. The welfare of honorary teachers in Indonesia is still a problem that must be resolved immediately. The low wages of honorary teachers in Indonesia cause many honorary teachers to take part-time jobs to meet economic needs. This research aims to seek legal protection for honorary teachers' wage rights, with the hope that honorary teachers have clear and definite legal protection so that honorary teachers can get wage rights commensurate with their hard work. This research uses normative legal methods. The results of this research show that there are still many cases of honorary teachers who are willing to work elsewhere to meet economic needs, some are even determined to sell illegal goods because of the low wages of honorary teachers. The absence of legal certainty governing salary schemes for honorary teachers is one of the causes of low wages for honorary teachers and also the absence of regulations that regulate honorary teachers.